Targeted Alpha Therapy Trial in Bangladesh: Promise for Advanced MUC1 – Expressing Tumors - Nisa, Lutfun; Quadir, Kamila Afroj; Begum, Shamim MF; Hussain, Raihan; Hasan, Mizanul (Bangladesh Journal of Nuclear Medicine, 2018)
Introduction: Targeted alpha therapy (TAT) is a new experimental therapy that targets cancer cells and tumor capillary endothelial cells through intravenous injection of an alpha immuneconjugate (AIC). The AIC is formed by labeling the cancer targeting vector (monoclonal antibody) with alpha emitting radioisotopes using a bifunctionalchelator. The monoclonal antibody (MAb) is raised against antigens (e.g. MUC1) over-expressed on the surface of certain cancer cells. There are several centers notably in Europe, the US and Australia that are actively involved in TAT clinical trials of different cancers using a variety of techniques, alpha emitters and MAbs. Observations from their cumulative experience suggest that TAT is safe and effectivebut needs further trials for practical acceptance. Especially critical is the issue of maximum tolerance dose (MTD) which needs to be established for maximum target kill. Bangladesh has the infrastructure to conduct aTAT clinical trial and can significantly add to the growing pool of data for advanced treatment of cancers through collaborative involvement in targeted alpha therapy research. Objective: The aim of the article is to present a general overview of targeted alpha therapy and to discuss the feasibility of a TAT clinical trial in Bangladesh in the context of current cancer management situation in the country. Method: Literature review of significant publications was done to obtain an update of the current status of targeted alpha therapy. Relevant issues of TAT are presented for a theoretical basis of the technology. Next, the methodology of a proposed clinical trial is discussed, together with the practicability of its introduction in Bangladesh. Conclusion: Implementation of TAT clinical trial will help to develop an advanced technology and build- up skilled manpower in Bangladesh.It will optimize the key parameters of targeted alpha therapy, i e stability and specific activity of the alpha-conjugate and establish the maximum tolerance dose for the AIC. If the clinical trial is successful, it can change the prognosis of many end-stage cancers. Patients in Bangladesh with advanced MUCI expressing tumors of the breast, ovary, pancreas and prostate can have some measure of hope with stability of the disease. Bangladesh J. Nuclear Med. 19(1): 43-50, January 2016